Pedagogical Conditions Of Professional Training Development Of Teachers Of Future Pre-School Educational Organizations - Ashirova Sojida Bakhramovna (Euro Asian Journal Publishing, 2023)
The content of the article covers the content and essence of the concept of a career in education, the types of careers used in science and the conditions for the formation of a professional career, and the content of the formation of the professional career of Educators of future preschool educational organizations. It has also been argued that various methods and techniques can be used to determine the attitude towards professional careers. According to the content of the data given, the concept of professional career is studied as the main topics of several publications, and sources are also given about this literature. It is established that the resources given in the article can be used in thematic research, classroom activities and organized pilot work on the content of Mazu.
Keywords: career; professional career; domestic career; vertical career